1999
DOI: 10.1192/bjp.174.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with in-patient psychiatric services

Abstract: There remain problems with satisfaction scales. Qualitative approaches to examine patients' experiences in hospital and the causes of dissatisfaction are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 14 publications
4
46
1
1
Order By: Relevance
“…However the limitation of this study once again was that it surveyed therapists rather than the women themselves. Greenwood et al(1999) Participants indicated that loss of control, experience of overt and implicit racism, unhelpful relationship with some professional staff and lack of activities as negative factors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However the limitation of this study once again was that it surveyed therapists rather than the women themselves. Greenwood et al(1999) Participants indicated that loss of control, experience of overt and implicit racism, unhelpful relationship with some professional staff and lack of activities as negative factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has been most apparent in the area of acute mental health, where traditionally service users have had limited opportunities to be equal partners in discussion and decision making processes about their own treatment and care (Greenwood et al 1999). This is due to the narrow view held by some professionals that service users might be too unwell to decide what they need or what is beneficial for them or be incapable of making decisions (Deegan, 1996;Trivedi, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative papers generally scored well for reporting the analysis used, but there was little or no acknowledgement of the impact of the researcher on the research process. The four mixed methods papers scored 0% (Lovell, 1995), 25% (Sweeney et al, 2014), 50% (Greenwood et al, 1999) and 75% (Ricketts, 1996) respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Five studies (Greenwood et al, 1999;Kohler et al, 2015;Ricketts, 1996;Smith et al, 2014;Sweeney et al, 2014) reported a mean score of the Client Satisfaction Questionnaire (CSQ-8/ZUF-8), with scores ranging from 21 to 26.8 (mean score 23.53). The CSQ-8 consists of a range of potential scores from 8 to 32, with higher scores indicating greater satisfaction.…”
Section: General Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation